IL-10 and TGF-β Induced Arginase Expression Contributes to Deficient Nitric Oxide Response in Human Visceral Leishmaniasis - Kupani, Manu; Sharma, Smriti; Pandey, Rajeev Kumar; Kumar, Rajiv; Sundar, Shyam; Mehrotra, Sanjana (Frontiers in Cellular and Infection Microbiology, 2021)
Nitric oxide (NO) is an anti-microbial effector of the innate immune system which plays major role in non-specific killing of various pathogens including protozoan parasites. However, due to subversion of the host’s immune processes by pathogens, suboptimal production of NO is frequently found in many infection models. Previous studies have shown suppressed NO production during Leishmania donovani infection, the causative agent of visceral leishmaniasis (VL). Availability of L-Arginine, a semi-essential amino acid is required for inducible nitric oxide synthase (iNOS) mediated NO production. However, arginase is another enzyme, which if expressed concomitantly, may strongly compete for L-Arginine, and suppress NO production by iNOS. In the present study, plasma nitrite and arginase levels were measured in VL patients before and after successful drug treatment, endemic and non-endemic healthy donors. We observed significantly lower NO levels in the plasma of VL patients as compared to endemic controls, which improved significantly post-treatment. Significantly elevated arginase activity was also observed in the plasma of VL patients, which may be associated with NO deficiency. VL patients also showed significantly higher levels of IL-10 and TGF-β, which are known to regulate expression of arginase in various immune cells. In vitro studies with human peripheral blood mononuclear cells (PBMCs) further corroborated the role of IL-10 and TGF-β in arginase mediated suppression of NO production.